2021 Canadian Thoracic Society Guideline – A focused update on the management of very mild and mild asthma. Issue 4 (27th January 2021) - Yang, Connie L.; Hicks, Elizabeth Anne; Mitchell, Patrick; Reisman, Joe; Podgers, Delanya; Hayward, Kathleen M.; Waite, Mark; Ramsey, Clare D.
Abstract: Background: This asthma guideline update focuses on the management of individuals with asthma at the mild end of the spectrum. It applies to children 1 year of age and over and adults. This update was initiated to address new clinical trials in this patient group as well as changes in the recommendations from the Global Initiative for Asthma (GINA) asthma strategy group. This guideline applies the current evidence to the Canadian context. Methods: A representative multidisciplinary panel of experts undertook a formal clinical practice guideline development process. A total of 9 key clinical questions were defined according to the Patient/problem, Intervention, Comparison, Outcome (PICO) approach. The panel performed an evidence-based, systematic literature review, assessed and graded the relevant evidence to synthesize 11 key recommendations. These recommendations were reviewed in the context of the existing Canadian Asthma Guidelines and changes from previous guidelines are highlighted. Results: The updated evidence demonstrated that daily inhaled corticosteroids (ICS) + PRN short-acting beta-agonist (SABA) decrease exacerbations and improve asthma control compared to PRN SABA in individuals with very mild and mild asthma. There is new evidence in children ≥12 years of age and adults that PRN budesonide/formoterol (bud/form) decreases exacerbations in comparison to PRN SABA, with different levels of evidence in those with very mild versus mild asthma. Individuals with very mild asthma at higher risk of exacerbation should be given the option of switching from PRN SABA to daily ICS + PRN SABA (all ages) or PRN bud/form (≥12 years of age). In individuals with mild asthma, daily ICS + PRN SABA are still recommended as first line controller therapy. However, in individuals ≥12 years of age with poor adherence to daily medication despite substantial asthma education and support, PRN bud/form is an alternative. Intermittent use of very high dose ICS for acute loss of asthma control is not suggested in preschoolers given potential for harm. Discussion: This guideline provides a detailed review of the evidence and provides recommendations for the treatment of very mild and mild asthma within the Canadian context for preschoolers, children and adults. The Canadian Thoracic Society 2021 Asthma Guideline update will amalgamate these recommendations with previous guidelines to provide a document that address diagnosis and management of asthma.